Perbedaan Hasil Pemeriksaan Hemoglobin dengan Point of Care Testing (POCT) pada Sampel Darah Vena dan Kapiler - Reza Widianto; Dwi Purbayanti; Rinny Ardina (Borneo Journal of Medical Laboratory Technology, 2021)
On examination of hemoglobin with POCT generally use capillary blood. The use of capillary blood as a test sample has a deficiency, namely the possibility of dilution in capillary blood samples caused by a deep puncture so that the blood that comes out is not smooth and usually the fingers will be pressed or sequenced. This condition can cause blood dilution by tissue fluid, so the test results will tend to be low. The purpose of this study was to find out the difference in hemoglobin results with POCT in venous and capillary blood samples. This study uses descriptive analytical methods that aim to describe or describe a situation objectively, and then describe it. The results showed the average hemoglobin level in the venous blood sample was 13.2 g/dl. While in capillary blood samples 12.9 g / dl. The results of the independent t-test obtained a significance value of 0.224 (p > 0.05) so it can be concluded that there is no significant difference between the results of hemoglobin levels examination using venous blood samples and capillary blood samples.